2008
DOI: 10.1179/102453308x316130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Epstein–Barr virus infection in adult T-cell leukemia

Abstract: The involvement of adult T-cell leukemia (ATL) cells in organs such as the skin and lymph nodes is observed in about 50% of cases of ATL. Epstein-Barr virus (EBV) infection has often been observed in the clinical course of ATL. In this study, we established two B-cell lines from peripheral blood of patients with ATL. EBV DNA, proviral DNA for HTLV-1 and Tax mRNA were detected in both lines. As part of the characterization of these cells, an enhanced expression of intercellular adhesion molecule-1 (ICAM-1) (CD5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…In addition to the high levels Luc transduction, we chose to use Raji/CD4 cells in the following experiments for several reasons. First, B-cells are natural targets for HTLV-1 infection in vivo and in vitro [35],[36],[37],[38],[39]. Furthermore, B-cells were shown to form conjugates (virological synapses) with HTLV-1-infected T cells in PBMC cultures from HTLV-1-infected individuals [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the high levels Luc transduction, we chose to use Raji/CD4 cells in the following experiments for several reasons. First, B-cells are natural targets for HTLV-1 infection in vivo and in vitro [35],[36],[37],[38],[39]. Furthermore, B-cells were shown to form conjugates (virological synapses) with HTLV-1-infected T cells in PBMC cultures from HTLV-1-infected individuals [14].…”
Section: Resultsmentioning
confidence: 99%
“…We are currently examining these possibilities. Although Raji/CD4 cells are not natural targets for HIV-1 infection, we believe that they do provide an appropriate model system to study HTLV-1 cell-to-cell infection, as B-cells are natural targets for HTLV-1 infection in vivo and in vitro [35],[36],[37],[38],[39] and can form synapses with HTLV-1-infected T lymphocytes in vitro [14]. While it is desirable to examine cell-to-cell infection using primary T-cells as targets, we have been unable to detect Luc transduction in cocultures of transfected Jurkat T-cells and activated CD4 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD21 is the EBV-receptor and is reported to be over expressed in CD4+ T cells in ATLL as a result of the stimulatory influence of the HTLV-1 Tax protein; however, evidence of EBV DNA integration could not be demonstrated in these cells, questioning the role of EBV in the ATLL leukemogenesis [11]. In contrast, a recent study purports that coinfection with HTLV-1 and EBV may be associated with a greater likelihood of organ involvement and a more aggressive course through the enhanced expression of adhesion molecules via increased IL-4 signaling [12]. …”
Section: Discussionmentioning
confidence: 99%
“…[11, 12]. Plausibly patients with ATLL may be more susceptible to this infection than patients with other types of lymphoma due to the levels of immunosuppression [1].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper in patients with ATLL, Ueda et al indicated that coinfection with HTLV-1 and EBV may induce a more extensive organ involvement through the enhanced expression of adhesion molecules via IL-4 signaling [21]. Similarly, Ogata et al found a subclinical reactivation of EBV in ATLL patients undergoing chemotherapy [22].…”
Section: Discussionmentioning
confidence: 99%